Pengaruh Kompensasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pt Pama Persada Nusantara Di Sangatta-Kutai Timur - Kaharuddin Kaharuddin (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2017)
The study tries to identify to what extent compensation and discipline for work performance of employees PT Pama Persada. Analysis model used to prove hypothesis is model analysis multiple linear regression that be analyzed with using statistics computer program package, that is SPSS v. 16.0 for Windows. Furthermore it was conducted examination for validity of data by multikolinieritas test, heteroskedasticity test and autocorrelation test. Result of statistics analysis show that coefficient of the free variables regression, that is involvement factor in compensation (X1) = 0,059, discipline (X2) = 0,743, and Constanta equal to 0,697. Equation of multiple linear regression is: Y = 0,697 + 0,059 X1 + 0,743 X2 Conclusion that receive that level of influence explained by compensation, discipline are as independent variable impact toward performance of employees PT Pama Persada equal to correlation coefficient (R), that is 0,766 and level of depended performance to second of free variables above is equal to determination coefficient value (R2) that is 0,587 or 58,7 %. The result of analysis F – test indicate that all free variables by together have significant influence toward the performance of employees PT Pama Persada. Variable independent has dominant influence to performance of employees PT Pama Persada is discipline.